TINGKAT, POLA, DAN DETERMINAN USIA KAWIN WANITA DAN PRIA* - Sukamdi Sukamdi; Susi Eja Yuarsi; Wini Tamtiari (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1995)
This study is conducted in three provinces, West Java, South Sulawesi and West Nusa Tenggara, which represent different cultural background, using secondary data namely marital verification forms (MVF). From methodological point of view this study finds that MVF can be used as data sources in analysing age of marriage inspiteof using population census or national surveys.The result of previous studies have not been confirmed by this study. Mean age at first marriage in West Java is not the lowest, but is West Nusa Tenggara. In addition South Sulawesi is always the highest. Cultural backgrounds such as dowery in South Sulawesi which is the highest among the provinces and the tradition of delopement in West Nusa Tenggara are very important in explaining the variation of age at first marriage. However education has also an important role as independent variable for age at first marriage.